Improvement of cardiac sympathetic nerve function in sarcoidosis - Smulders, N.M.; Bast, A.; van Kroonenburgh, et al., M.J.P.G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Some patients with sarcoidosis can have cardiac involvement. Impairment of the cardiac sympathetic nerve activity is seen in about 50% of the sarcoidosis patients with small fiber neuropathy. In this case we present a sarcoidosis patient with small fiber neuropathy and cardiac symptoms with a cardiac sympathetic dysfunction, assessed with I-123 MIBG SPECT. After 5 months of treatment with carvedilol, which has besides adrenergic receptor blocking effects also antioxidant action, we saw a clear improvement of the cardiac sympathetic function demonstrated on a repeated I-123 MIBG SPECT. Future studies should explore the clinical relevance of the relation of oxidative stress, antioxidant therapy and cardiac dysfunction in sarcoidosis.